2019
DOI: 10.20961/carakatani.v35i1.29336
|View full text |Cite
|
Sign up to set email alerts
|

The Customer Satisfaction Analysis of Community based Agrotourism in Yogyakarta

Abstract: Several kinds of agro-tourism are managed by the community and by the private sector. However, if agro-tourism is managed by the community, can it give satisfaction to the visitors? This study aims to determine the level of customer satisfaction by Customer Satisfaction Index (CSI) and to investigate what marketing mix attributes should be improved by IPA-Kano integration analysis. The research method used was a quantitative research on community-based Salak (<em>Salacca zalacca</em>) Agro-tourism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
(21 reference statements)
1
5
0
1
Order By: Relevance
“…This has resulted in these attributes having a low level of suitability, especially inadequate health facilities, parking lots, maps of attractions, restrooms and places of worship. This is in line with Indrayanti et al, (2019), stated that service attributes that can increase visitor satisfaction are variations in tourism attractions, infrastructure, and adequate facilities including toilet cleanliness.…”
Section: Results and Discussion Suitability Level Of Performance And ...supporting
confidence: 81%
See 2 more Smart Citations
“…This has resulted in these attributes having a low level of suitability, especially inadequate health facilities, parking lots, maps of attractions, restrooms and places of worship. This is in line with Indrayanti et al, (2019), stated that service attributes that can increase visitor satisfaction are variations in tourism attractions, infrastructure, and adequate facilities including toilet cleanliness.…”
Section: Results and Discussion Suitability Level Of Performance And ...supporting
confidence: 81%
“…Many agro-tourism destinations had given satisfaction to visitors, but most of them cannot depend on one agro-tourism. According to Indrayanti et al, (2019) almost all visitors only come once to enjoy the agro-tourism services provided. Furthermore, Sugandini et al's (2018) primary data analysis showed that the quality, satisfaction, and visitor perceptions of tourism imagery were not in line with the level of visitor loyalty.…”
Section: Customer Satisfaction Index (Csi)mentioning
confidence: 99%
See 1 more Smart Citation
“…Agrotourism is a series of travel activities that utilize the location or agricultural sector from the beginning of production to obtain agricultural products in various systems and scales to expand, knowledge, understanding, experience, and recreation in the field of farming (Indrawati et al, 2020). This shows that agrotourism not only offers agricultural products to visitors but also offers services to make visitors feel satisfied and entertained and can even have the ability to better understand the agricultural sector (Indrayanti et al, 2020).…”
Section: B Literature Review Agrotourismmentioning
confidence: 99%
“…Kontrasepsi Implan dapat dipasang wanita hari ke-2 sampai hari ke-7 setiap saat selama siklus haid. Implan juga merupakan kontrasepsi jangka panjang yang aman untuk pemasangan pasca lahir, baik pada wanita yang ingin menyusui maupun tidak (Rocca et al, 2021;Schreiber & Barnhart, 2019 (Gunawan & Iqbal, 2018;Indrayanti et al, 2020;Kusumarini et al, 2022;Nuraina et al, 2021;Prakoeswa et al, 2022;Seftylia & Cholil, 2021), namun penelitian terkait kepuasan akseptor terhadap pelayanan pemasangan kontrasepsi implan pada fasilitas kesehatan menggunakan analisis CSI pasca pandemi Covid-19 belum banyak dilakukan terutama di Indonesia.…”
unclassified